The growth of Huaqiandai Secret-recipe Grilled Fish - Li, Dongxian (London : Renmin University, 2022)
Huaqiandai Secret-recipe Grilled Fish, a catering brand based in Henan province, has now become the third best known grilled fish brand in China since its founding in 2012, owing to its product and franchising strategies oriented to customers' needs. Its business has expanded from Zhengzhou city of Henan to the whole China, even abroad. In 2020, Huaqiandai withstood the test of Covid-19 epidemic, maintaining a sustained growth in performance and with more than 20 franchised restaurants added. This case describes the development process of Huaqiandai from its establishment to a firm foothold in the market, as well as the thoughts of the founder, marketing issues during the development of the brand, inspiring students' thinking in product R&D, channel expansion and emergency response.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Branding (Marketing) -- China; Crisis management -- China